The Impact of Project-Based Learning on Students’ Cultural Awareness - AKHARRAZ, Mohamed (International Journal of Language and Literary Studies, 2021)
While only a few studies have been conducted to explore the effectiveness of project-based learning (PjBL) in culture teaching/learning in second and foreign language education, no study known to the investigator has empirically measured the effect of PjBL together with the cultural framework of the 3Ps (products, practices, and perspectives) in the teaching of culture in an EFL context. This study aimed to measure the effect of PjBL on students’ awareness of the English cultures. Two intact groups at a Moroccan public school were randomly assigned to control and treatment groups. A cultural awareness test was utilized to measure students’ cultural awareness levels before and after a 24-week treatment. The independent sample t-tests indicated that the PjBL group substantially outperformed the control group in cultural awareness. While the study concluded that PjBL is a useful tool for incorporating cultures in the EFL classes, its proper implementation entails a redistribution of power in the language classroom and a radical change in the culture of assessment.